RENAL AND MYOPATHY LESIONS OF DIROFILARIA IMMITIS IN NATURAL INFECTED DOGS (Iraqi Journal of Medical Sciences, 2016)
Background: Dirofilaria immitis has been increasingly recognized worldwide as inadvertent human pathogens. The epidemiological survey usual hosts of theses nematodes are domestic and wild carnivores. The disease is regarded as one of the most dangerous threat for the dog health. The adult worms take up residence in the heart, lungs and surrounding blood vessels.Objective:This study attempts to shed the light on relationship between glomerular lesions and heart filarial (Dirofilaria immitis) infection.Methods: Dirofilaria immitis was isolated from 98 dogs out of 457 dogs that were autopsied for the time between April 2008 and May 2010, in Al-Hindya area, Karbala province. Parameters concerning parasitological and pathological changes are used in this study to determine the significance of the results.Results:Grossly many adult heartworms were found in the right ventricle of infected hearts and the cross section revealed body cavity, thick cuticle with coelomyarian and polymyarin muscle type, accompanied by infiltration of inflammatory cells mainly eosinophils and lymphocytes between muscle fibers. The microscopical changes in the kidney were necrotic and sloughing of epithelial cells, cystic dilation of collecting tubules of medulla containing hyaline casts, with glomeruli showing membranous nephropathy.Conclusions:This is the first histological report of canine filariasis in Iraq particularly in Karbala province. It is important to keep in mind that pathologic changes in heartworm disease may be well advanced before the appearance of clinical signs of the disease. In heartworm disease the circulatory system is not the only system affected. The renal, hepatic & pulmonary systems can be secondarily affected. In our work the observations support the previous hypotheses of immature and possibly adult worms, contribute to the glomerulonephropathy.Key wards :Canine heartworm, interstitial nephritis, membranous nephropathy.